2022
DOI: 10.3390/d14020131
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Wood-Decaying Fungi in Wuliangshan Area, Yunnan Province, P.R. China

Abstract: Five surveys were carried out in the Wuliangshan area, Yunnan Province, P.R. China, based on a combination of morphological features and molecular evidence. Around 2454 specimens of wood-decaying fungi were collected. The paper summarizes the obtained results on the wood-decaying fungi of this area, consisting in 95 species distributed in 59 genera, 23 families and 9 orders. Their hosts and substrates were also identified. A checklist of wood-decaying fungi is given. Sequences of the ITS nrRNA gene region of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Over the past ten years there has been a colossal advance in the classification and description of novel species of fungi. This has mainly been due to the use of molecular tools, but also more research efforts being carried out in prosperous, previously developing nations, such as Brazil, China and Thailand (Hyde et al 2018b , 2021 ; Boonmee et al 2021 ; He and Zhao 2022 ). Publication outlets such as Fungal Diversity Notes (Hyde et al 2020a ; Yuan et al 2020 ; Boonmee et al 2021 ), Fungal Planet (Crous et al 2020a , b , 2021a ; b ) and Mycosphere notes (Pem et al 2019 ; Hyde et al 2021 ) have introduced more than 2000 novel taxa.…”
Section: Fungal Diversitymentioning
confidence: 99%
“…Over the past ten years there has been a colossal advance in the classification and description of novel species of fungi. This has mainly been due to the use of molecular tools, but also more research efforts being carried out in prosperous, previously developing nations, such as Brazil, China and Thailand (Hyde et al 2018b , 2021 ; Boonmee et al 2021 ; He and Zhao 2022 ). Publication outlets such as Fungal Diversity Notes (Hyde et al 2020a ; Yuan et al 2020 ; Boonmee et al 2021 ), Fungal Planet (Crous et al 2020a , b , 2021a ; b ) and Mycosphere notes (Pem et al 2019 ; Hyde et al 2021 ) have introduced more than 2000 novel taxa.…”
Section: Fungal Diversitymentioning
confidence: 99%
“…In the present study, a total of 1,407 specimens belonging to 74 wood-decaying poroid and corticioid species were collected from Zixishan area, including 63 white rot species (85.14% of the total) and the remaining 11 brown-rot species (14.86% of the total). In contrast, the proportion of brown-rot fungi in Zixishan area is similar to that in Huangshan Mountains, which is 14.12% (Cui & Jia 2011), and it is higher than Wuliangshan area and Haikou Forestry compared to 5.26% and 6.12% (He et al 2021, He & Zhao 2022), but it is lower than Great Xingan Mountains compared to 26.19% (Cui & Yu 2011) In forest ecosystems, wood-inhabiting poroid and corticioid fungal function as wood decomposers release matter and energy to the ecological system (Cui et al 2006, Wei 2010, Gafforov et al 2020. Combined nLSU, SSU, 5.8s, rpb1, rpb2, and tef1 phylogenetic analyses in the subphyla Agaricomycotina, Pucciniomycotina and Ustilaginomycotina, showed that 1928 currently used genera names are distributed in 241 families, 68 orders, 18 classes and four subphyla.…”
Section: Discussionmentioning
confidence: 76%
“…The present work is the first report of a series of studies devoted to wood-decaying fungi in this area and contributes to revealing the abundance of wood-decaying species. According to the previous studies (Dai 2011, 2012, 2021, He & Zhao 2022) combined with field observations, the Wuliangshan area reported 90 white-rot fungi and five brown-rot fungi and Haikou Forestry Park reported 46 white-rot fungi and three brown-rot fungi, and Huangshan Mountains reported 73 white-rot fungi and 12 brown-rot fungi, and Great Xingan Mountains reported 93 white-rot fungi and 33 brown-rot fungi. In the present study, a total of 1,407 specimens belonging to 74 wood-decaying poroid and corticioid species were collected from Zixishan area, including 63 white rot species (85.14% of the total) and the remaining 11 brown-rot species (14.86% of the total).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hjortstam, now typified as the type species. Gyrodontium sacchari is a cosmopolitan species, with hotspots of occurrence mainly in pantropical areas of the world; it has been reported from all continents except Antarctica (Carlier et al 2004;Bernicchia and Gorjón 2010;Robledo et al 2014;He and Zhao 2022).…”
Section: Notes On Geographic Distributionmentioning
confidence: 99%